Extraction and characterization of purple pigment from chromobacterium violaceum grown in agricultural wastes - Neshati, Akram (2010)
There has been an increasing trend towards replacement of synthetic colorants with natural pigments in last decades because of the strong consumer demand for more natural products. Among three groups of main natural pigments, bacterial pigments are considered as an alternative to synthesized dye. Production and extraction of violet pigment of Chromobacterium violaceum grown on agricultural waste such as solid pineapple waste (SPW) and brown sugar (BS) was studied. From the study, the optimum growth temperature of C. violaceum and pigment production is at 25°C and optimum pH is 7. The pigment was extracted from the growth media using two solvents which were methanol and ethyl acetate. Characterization of the purple pigment was carried out using UV-VIS spectrophotometer, FTIR and 1H and 13C-NMR. UV-VIS analysis of the purple pigment samples from nutrient broth (NB), BS and SPW media shows ?max at 566.50, 567.50 and 571.94 nm respectively. FTIR spectrum of purple pigment pellet from BS growth medium showed a broad peak at 3430.10 cm-1 assigned to OH stretching, overlapping of N-H bond with O-H stretching observed at 3330.1 cm-1, two stretching bonds at 1640 cm-1 and 1723.5 cm-1 assigned to the C=O amide groups and C=C peak at 1615.92 cm-1. 1H-CNMR and 13C-NMR spectra were recorded in DMSO-d6 and 20 carbon peaks and also 13 proton peaks appeared in the result to confirm the present of violacein in the samples. Lastly, stability of the produced pigment towards changes of the pH was examined. The pigment shows different colors at different pH.